Perbandingan Pengaruh Latihan Core Stability Dengan Zig Zag Run Terhadap Agility Pada Pemain Sepak Bola Cabang Aceh Barat Daya - Miftahul Zannah; Mifthah Rezqiyah (Universitas Widya Husada Semarang, 2022)
As a soccer athlete, having good agility has several advantages, including being easy to perform difficult movements, not easily falling and causing injury. Agility can be improved with core stability exercises and zig zag runs. This experiment was indentified to find out the difference in the effect of core stability training with zig zag run on increasing agility in Southwest Aceh soccer players in 2021. Respondent of this experiment are 16 people (n=16) met the inclusion criteria with 8 people in the core stability group and 8 people in the zig zag run group. The research method used is a quasi-experimental approach with two groups of pre and post test designs. The data collected was first tested for normality with the Shapiro Wilk test (n=<50), the results obtained were 0.179 (preZigzag), 0.321 (preCoreStability) meaning the data was normally distributed (p>0.05). Then the homogeneity test was carried out with the Levene test, the value (sig) of 0.863 (p>0.05) means that there is a similarity of variance (homogeneous) between groups. Statistical analysis in both groups used Paired Sample t-test and obtained a sig value for the core Stability group of 0.000 and for the Zigzag Run group of 0.000, it can be concluded that there was a difference after being given treatment in each treatment group (p <0.05). Different test of the effect of post test core Stability and zigzag Run using the Independent Sample t-test and obtained a value (sig) of 0.015. So it can be concluded that there is a difference between the treatment of group I and group II (p<0.05). The conclusion is a difference in the effect of core stability and zigzag run training on increasing agility in soccer players.